PEREMPUAN DALAM DUNIA KERJA (COPING STRATEGY PEREMPUAN PEKERJA DI TVRI KETIKA MENGALAMI DISKRIMINASI - Mila Candra Novianti; wiwid Noor Rakhmat (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Gender discrimination in the television industry is background of the research. The more dominated organizational structure and environment of men led to discriminatory treatmen of women. The research aims to describe how women survive in discriminatory environments. Studies using female subjects who working at television stations of TVRI include presenter dan reporter. This research uses muted group theory and coping strategies theory. Research isi a descriptive qualitative study using critical phenomenology approach, data collection with in depth interviews. Research data show that women who work in the television industry especially TVRI, have gotten discriminatory treatment from coworkers or male superiors. Such treatment is inferiority, subordination, stereotypes, marginalization and sexual harassment. Over time treatment is less frequent than in any previous years. Discrimination treatment makes some women feel they can’t freely express themselves and tend to restrict themselves with male coworkers. When profaced discrimination like sexual harassment, not every women has the courage to speak up and defend herself, but chose to be silent and evasive. Justice has not been fully felt by some women who work at TVRI. Research concludes that some women who work on television especially TVRI are either presenter or reporters had discriminating before, but that is kind of rare now. Discriminatory treatment exposes women to silence and does not freely voice what is felt.